Outcomes and Impacts of Development Interventions: Toward Conceptual Clarity - Belcher, B.; Palenberg, M. (SAGE Publications, 2018)
The terms “outcome” and “impact” are ubiquitous in evaluation discourse. However, there are many competing definitions that lack clarity and consistency and sometimes represent fundamentally different meanings. This leads to profound confusion, undermines efforts to improve learning and accountability, and represents a challenge for the evaluation profession. This article investigates how the terms are defined and understood by different institutions and communities. It systematically investigates representative sets of definitions, analyzing them to identify 16 distinct defining elements. This framework is then used to compare definitions and assess their usefulness and limitations. Based on this assessment, the article proposes a remedy in three parts: applying good definition practice in future definition updates, differentiating causal perspectives and using appropriate causal language, and employing meaningful qualifiers when using the terms outcome and impact. The article draws on definitions used in international development, but its findings also apply to domestic public sector policies and interventions.